Monitoring the Formation of Amyloid Oligomers Using Photoluminescence Anisotropy - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Flores-Vergara, E; Flores-Vergara, E (American Chemical Society, 2019)
The formation of oligomeric soluble aggregates is related to the toxicity of amyloid peptides and proteins. In this manuscript, we report the use of a ruthenium polypyridyl complex ([Ru(bpy)2(dpqp)]2) to track the formation of amyloid oligomers at different times using photoluminescence anisotropy. This technique is sensitive to the rotational correlation time of the molecule under study, which is consequently related to the size of the molecule. [Ru(bpy)2(dpqp)]2 presents anisotropy values of zero when free in solution (due to its rapid rotation and long lifetime) but larger values as the size and concentration of amyloid-β (Aβ) oligomers increase. Our assays show that Aβ forms oligomers immediately after the assay is started, reaching a steady state at ∼48 h. SDS-PAGE, DLS, and TEM were used to confirm and characterize the formation of oligomers. Our experiments show that the rate of formation for Aβ oligomers is temperature dependent, with faster rates as the temperature of the assay is increased. The probe was also effective in monitoring the formation of α-synuclein oligomers at different times. © 2019 American Chemical Society.